MINERALISASI NITROGEN TANAH PADA BERBAGAI PENGELOLAAN TANAMAN KOPI (Coffea L.) DI KECAMATAN TUTUR-PASURUAN - Novita Risti Azahra; Wanti Mindari; Setyo Budi Santoso (Plumula : Berkala Ilmiah Agroteknologi, 2021)
The mineralization process is responsible for the availability of N in the soil. The purpose of this study is to examine the management of coffee land (Coffea L.) and climate on the rate of soil Nitrogen mineralization. In situ incubation research by implanting 15.5 cm long cylindrical pvc ring; diameter of 14 cm that has been perforated around it and a wire covering / net so that animals such as scorpions and snakes do not enter the hole. The research was arranged in factorial randomized block design which was repeated 3 times. Factor 1 : 3 types of land management and factor 2 : 4 types of organic matter. The level of N mineralization is evaluated against the levels of N-nitrate and N-ammonium soil. The highest NH4+ N concentration of 0.060% was found in the L1S3 treatment (first land, mixed ring) and the lowest NH4+ concentration in the L3S1 treatment (third land, control ring) 0.03%. NO3 concentration - interaction occurs with the highest NO3 concentration in the L2S3 treatment (second land, mixed ring) 0.092% and lowest NO3 concentration in the L1S1 treatment (first land, control ring) 0.013% with a BNT value of 5% at 0.023%. So the fastest nitrogen mineralization occurs in soils that get litter of shade plants (mixed / S3). The value of mineralization rate is strongly influenced by temperature, the increase in the value of mineralization rate due to temperature is due to the faster process of decomposition of organic matter.